A One-Pot Synthesis of Highly Functionalized Indolizines by 1,3-Dipolar Cycloaddition of Azomethine Ylides and Phosphorylated Hydroxyketenimines - Yavari, Issa; Naeimabadi, Maryam; Hosseinpour, Reza; Halvagar, Mohammad Reza (Synlett, 2016)
Alkyl 2-(alkylamino)-3-(quinolin-2-yl)indolizine-1-carboxylates were prepared by1,3-dipolar cycloaddition of azomethine ylides with phosphorylated hydroxyketenimines, generated in situ by a Nef isocyanide–Perkow cascade.
Keywords: Nef reaction; Perkow reaction; cascade reaction; indolizines; dipolar cycloaddition; azomethine ylides